2016
DOI: 10.1371/journal.pone.0167135
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Generates Oxidative Stress and Induces Apoptosis in Adult Schistosoma mansoni Worms

Abstract: Inducing apoptosis is an interesting therapeutic approach to develop drugs that act against helminthic parasites. Researchers have investigated how curcumin (CUR), a biologically active compound extracted from rhizomes of Curcuma longa, affects Schistosoma mansoni and several cancer cell lines. This study evaluates how CUR influences the induction of apoptosis and oxidative stress in couples of adult S. mansoni worms. CUR decreased the viability of adult worms and killed them. The tegument of the parasite suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 76 publications
1
29
0
3
Order By: Relevance
“…Many drugs exert their negative effects on cancer cells are through increased the production of ROS [13, 14]. Mitochondrial dysfunction (MtD) represents a malfunction in biochemical processes, characterized by MMP collapse and decreased ATP production, also have an essential role in mediation of apoptosis [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs exert their negative effects on cancer cells are through increased the production of ROS [13, 14]. Mitochondrial dysfunction (MtD) represents a malfunction in biochemical processes, characterized by MMP collapse and decreased ATP production, also have an essential role in mediation of apoptosis [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, crude plant material is considered active on snails at concentration equal to or less than 100 ppm (μg mL −1 ), killing 90% of exposed snails. In addition, for isolated compounds, a molluscicidal candidate should be active at less than 20 ppm (μg mL −1 ) or present a LC 50 value lower than 40 ppm (μg mL −1 ) . Thus, this study demonstrated that CUR possesses potential activity against B. glabrata embryos with a LC 50 value of 6.54 μg mL −1 and causes mortality of newborn and adult snails (LC 50 values of 42.29 μg mL −1 and 87.69 μg mL −1 , respectively).…”
Section: Discussionmentioning
confidence: 82%
“…In this context, the decision to investigate CUR was triggered by a previous study employing the formulation of a curcumin‐nisin polylactic acid nanoparticle, which demonstrated moderate molluscicidal activity against adult and juvenile B. pfeifferi snails and lower activity against embryos . In addition, CUR possesses in vitro activity against adult worms of Schistosoma species and S. japonicum cercariae, exhibits in vivo schistosomicidal activity against S. mansoni and induces immunomodulation of granulomatous inflammation and haspotential antifibrotic activity, reinforcing the potential role of this compound against schistosomiasis. In addition, recent literature reports that CUR is interesting as it is inexpensive and shows lower toxicity in human and non‐targeted organisms .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations